Substitusi Pasir Besi Dengan Bestmitell Terhadap Nilai Kuat Tekan Dan Porositas Beton - Rifki Pratama; Lilis Zulaicha; Retnowati Setioningsih (Retii, 2021)
ABSTRACT This research was conducted to determine the compressive strength and porosity of concrete with variations of 0%, 5%, 15%, 25% iron sand as a substitute for fine aggregate and variations of 0%, 0.3% bestmitell as an additive to concrete mixtures. This research is also intended to compare concrete with or without Bestmitell added materials. The test was carried out at the age of 41 days, with a cylindrical specimen with a height of 30 cm and a diameter of 15 cm, with a total of 48 specimens. The results of testing the average compressive strength of normal concrete (BN) were 26.233 MPa. The results of testing the average compressive strength of iron sand concrete without bestmitell are at (BP15) with a compressive strength of 26.270 MPa. The test results for iron sand concrete and bestmitell were highest at (BP2503) with a compressive strength of 31.780 MPa. The results of the porosity test in each test object increased from normal concrete (BN) with a porosity of 1.39%. In this study, the effect of porosity is very small; to the compressive strength of concrete with a coefficient of R2 = 0.0015 and R2 = 0.1956. Keywords: Concrete, Iron Sands, Bestmitell, Compresstion strength, Porosity.